Playing with tradition in communities of Swedish folk music: Negotiations of meaning in instrumental music tuition - Tullberg, Markus; Sæther, Eva (Frontiers in Education, 2022)
The present article explores meaning in relation to musical learning. A point of departure is the assumption that a meaningful music education is strongly related to the social domain of music making, and the aim of this article is to provide analytical tools with which to understand how meaning is negotiated within instrumental music tuition. Our interest lies in formal higher music education, an arena where the social dimension tends to be rather obscure, in contrast to the genre of Swedish folk music which is our empirical context. There is a strong case for revaluation of the social dimension in the study and creation of a meaningful music education. In line with this, our analytical framework draws primarily upon theories of situated cognition, situated learning, and communities of practice. In particular our analytical focus is negotiations of meaning, which are understood as constituted by two reciprocal processes of participation and reification. Meaning, understood in this way is thus a process that is incomplete, ongoing, and open-ended. Since negotiations of meaning refer to a larger picture, they become a useful point of focus in understanding the dynamics between a single learning situation, the educational framing, and the wider musical world of the learner. We exemplify how this analytical perspective can be applied by referring to our ongoing research project, which investigates trajectories of learning within different communities of Swedish folk music. We focus on two analytical nodes that have bearing across the communities, and which in themselves are locus points around which meaning negotiations continuously evolve: (i) the identity of spelman and (ii) the approach to notation. With these two examples we hope to show the potential of the framework. We also present methodological considerations that come from applying the proposed analytical tools in our study. Using an ethnographic approach, we lean towards the ideas of “messy research”, musical research sensibilities, and step-wise deductive induction. In the final section of the article, we elaborate on the educational implications that follow from a perspective that takes meaning as its point of departure.